2007
DOI: 10.3177/jnsv.53.191
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Alfacalcidol on Cancellous and Cortical Bone Mass in Rats Treated with Glucocorticoid: A Bone Histomorphometry Study

Abstract: RetractionThe following articles have been retracted by the Editorial Board of Journal of Nutritional Science and Vitaminology, because some parts of their contents were published in other journals. , 191-197, 2007 J Nutr Sci Vitaminol , 53 , 191-197, 2007 191 Summary The beneficial effects of alfacalcidol (ALF) on bone mass, bone formation, and bone resorption have been established in ovariectomized rats. Our previous studies showed that high-dose glucocorticoid (GC) administration (methylprednisolone sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…In addition, the present study is the first study to demonstrate an osteo-protective benefit of GTP and 1- α -OH-vitamin D 3 . Such an action of preserving bone mass in the LGD group agrees with those data previously reported for GTP supplementation [11, 18] or 1- α -OH-vitamin D 3 administration [29, 31, 35, 47, 48] in various bone loss models.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the present study is the first study to demonstrate an osteo-protective benefit of GTP and 1- α -OH-vitamin D 3 . Such an action of preserving bone mass in the LGD group agrees with those data previously reported for GTP supplementation [11, 18] or 1- α -OH-vitamin D 3 administration [29, 31, 35, 47, 48] in various bone loss models.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, alfacalcidol has become more popular in the treatment of bone loss-related diseases [30–34]. Studies have shown that alfacalcidol mitigated bone loss in a model of glucocorticoid/inflammation-induced osteoporosis [30] as well as a model of osteoporosis in rheumatoid arthritis [35, 36] due to its anti-inflammatory effect. However, the effect of 1- α -OH-vitamin D 3 on chronic inflammation-induced bone loss along with possible mechanism(s) has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Tea has been reported to have beneficial effects in various inflammatory conditions, such as carrageenan-induced paw edema [13], inflammatory bowel disease [14], collagen-induced arthritis [15] or lipopolysaccharide (LPS)-induced gingival inflammation [16]. On the other hand, alfacalcidol (1-α-OH-vitamin D 3 , a hydroxylated form of vitamin D) was also shown to mitigate bone loss in a model of glucocorticoid/inflammation-induced [17,18] or rheumatoid arthritis-induced bone loss [9,19] due to its anti-inflammatory property. However, the molecular mechanism(s) of green tea's or alfacalcidol's anti-inflammatory property in protecting deterioration of bone microstructure due to chronic inflammation has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of variation of these measurements at our laboratory was !1 . 0% (Iwamoto et al 2007, Shen et al 2008.…”
Section: Femoral Bone Area Bmc and Bmdmentioning
confidence: 99%
“…A has been effectively used to prevent glucocorticoid-induced bone mineral loss in laboratory animals (Turnquist et al 1992, Iwamoto et al 2007. However, the efficacy of A in preventing bone loss induced by L is not known.…”
Section: Introductionmentioning
confidence: 99%